Parenteral feeding in acute haemorrhagic pancreatitis - Domínguez, Carlos; Bertullo, Hugo; Olano, Estela; Barrial, Neldi; Imperial, Olga; Ferradas, Ana; Seijas, Rosario (Cirugía del Uruguay, 1989)
Authors stuied the nutritional management of 15 patients suffering from acute haemorrhagic pancreatitis. Diagnosis was made surgically in all cases; the etiology was biliar or idiopathic. Organ failure was frequent, as well as metabolic disorders, which demonstrate the severity of this illness, with a 46,6% mortality.